Awareness Regarding Acute Respiratory Tract Infection among Mothers of Under Five Children in a Tribhuvan University Teaching Hospital, Kathmandu - Ghimire, Rajina (Journal of Nursing Education of Nepal, 2022)
Background: Acute respiratory tract infection is the second leading cause of childhood morbidity and mortality among under-five years children and its prevalence is still high in Nepal. Awareness among parents regarding acute respiratory infection is important. The objective of the study was to find out awareness regarding acute respiratory tract infection among mothers of under-five children in maternal and child health clinic . Methods: A descriptive cross-sectional study was carried out at maternal and child health clinic of Tribhuvan University Teaching Hospital. Total 106 sample were selected by using non-probability purposive sampling technique. A face- to-face interview using semi- structured questionnaire was used to collect data. Collected data was analyzed by using descriptive and inferential statistics. Results: This study found that two third (62.3%) of respondents had an adequate level of awareness and more than one third (37.7%) had moderately adequate level of awareness of acute respiratory tract infections. More than two-thirds (75.5%) of respondents answered virus/bacteria as the main cause. Noisy breathing, difficulty breathing, cough, fever, runny nose, sore throat. ear discharge/ear pain was signs and symptoms. Almost one third (32.1%) of respondents knew cyanosis is a danger sign. The significant association was found between age (at p=0.026) and family size (at p=0.002) with level of awareness on acute respiratory tract infections. Conclusion: The study concluded that nearly two-thirds of mothers have an adequate level of awareness regarding acute respiratory tract infections. This study might be useful to carry out different health promotion-related activities and intervention by concerned stakeholder.